An Analysis of Phonological Errors of Children with Intellectual Disabilities in Special Schools and its Correlation with Islamic Education - Novelti, Novelti; Fitri, Laila; Pohan, Ratna Sari Dewi; Afdaleni, Afdaleni; Kamaliah, Kamaliah (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
Phonological error analysis in this study is related to the pronunciation of sounds of language in communication. Given the importance of communication between speakers and listeners, it is imperative to conduct a study of the analysis of children with intellectual disability's phonological errors. This study aims to analyze phonological errors consisting of phonetics and phonemics in the vocabulary of children with intellectual disability in SLB (Special School) Insan Mandiri, Tanah Pak Lambiak Village, Padangpanjang City. The method employed was the descriptive qualitative method. The data collection method was the listening and speaking method called the Simak Libat Cakap (SLC) technique. The instruments were the researchers, 200 basic Morris Swadesh vocabularies, stationery, and recording devices (cellphones). Data analysis techniques employed were (1) classify, (2) describe, (3) analyze, (4) discuss or implement, and (5) conclude. Based on the findings, phonological errors generally occurred in the phonetic domain, especially in pronouncing vibration sounds due to an illness that inhibits the speaking process of children with intellectual disabilities. Several errors were found in the pronunciation of consonants and clusters in the phonemic domain. Therefore, constant attention, guidance, and practice are needed so children with intellectual disabilities can communicate well. In Islam, education is considered one of the important aspects of life. Thus, the principles of inclusion and attention to individuals with intellectual limitations should be applied to children with intellectual disabilities. The ultimate goal is to ensure that all individuals have equal access to religious education and moral values that are important in the Islamic religion.